Analisis Program Bantuan Pengembangan Usaha Ekonomi Produktif (PUEP) Bagi Koperasi di Kabupaten Tegal - Oke Setiarso (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2008)
This research is proposed to analyze the results of The Development Programme of Business Productives to supported the Cooperations Development of Tegal Regency.This analysis shows that of The Development Programme of The business productive of The Cooperations in generally to influenced financials perspective ,members and markets servicing perspective but not to influenced either organization perspective or partnerships perspective of the Cooperations Development. Key words: The Development Program of Business Productives, Cooporation, The Cooperations, Development Ladder Assesment (DLA) .